Mediation by Firm Competence on the Relationship between Information Technology and Competitiveness of Consultancy Firms in Nairobi County, Kenya - Mugambi George M Nchebere, Tanui Joel K1 , Kilika James M (International Journal of Scientific Research and Management (IJSRM), 2017)
The business environment is constantly changing according to the influence of competitive forces and other environmental factors. Firms respond to the conditions surrounding them by adjusting their purpose and shape via deployment of appropriate strategic capabilities to match the environmental challenges and enhance competitiveness. Increasingly many firms have resorted to heavy investments in IT capabilities, to cope with the changing business environment. However, only some firms receive pay offs while manyothers do not. This study is of the view that the difference in competitiveness of firms with respect to the heavy IT investments is in how the individual firm competence mediates the deployment IT capabilities.However, there is scarcity of information on mediation of firm competence on the deployment of ITcapabilities as a source of competitiveness.